Determinants of Export Volume Oil Indonesian Raw Materials to Main Destination Countries - Anak Agung Istri Prami Suari Pemayun; Anak Agung Bagus Putu Widanta (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Crude Oil, which has long been a mainstay sector in Indonesia's exports, contributes greatly to state revenue, thus driving the pace of national economic growth. In the context of the Indonesian economy, the crude oil industry plays an indispensable role, especially over the past few decades. This study aims to identify the factors that affect the volume of Indonesia's crude oil exports to nine main destination countries—including Japan, South Korea, China, Thailand, Singapore, Malaysia, Australia, the United States, and Taiwan—in the period from 2003 to 2022. Some of the variables analyzed include exchange rates, foreign investment, production, and world oil prices. Through the regression analysis method of panel data, the results of this study indicate that simultaneously, exchange rates, foreign investment, production, and world oil prices have a significant effect on Indonesia's crude oil exports to these countries. Separately, the world exchange rate and oil price variables had a significant negative influence on Indonesia's crude oil export volume, while the foreign investment and production variables showed a positive and significant influence on export volume during the 2003-2022 research period.